Absence of interleukin-10 reduces progression of shiga toxin-induced hemolytic uremic syndrome. Issue 3 (12th February 2021) - Pineda, Gonzalo Ezequiel; Rearte, Bárbara; Todero, María Florencia; Bruballa, Andrea Cecilia; Bernal, Alan Mauro; Fernandez-Brando, Romina Jimena; Isturiz, Martin Amadeo; Zotta, Elsa; Alba-Soto, Catalina Dirney; Palermo, Marina Sandra; Ramos, María Victoria
Abstract: Hemolytic Uremic Syndrome (HUS), a disease triggered by Shiga toxin (Stx), is characterized by hemolytic anemia, thrombocytopenia and renal failure. The inflammatory response mediated by polymorphonuclear neutrophils (PMNs) and monocytes is essential to HUS onset. Still, the role of anti-inflammatory cytokines is less clear. The deficiency of IL-10, an anti-inflammatory cytokine, leads to severe pathology in bacterial infections but also to beneficial effects in models of sterile injury. The aim of this work was to analyze the role of IL-10 during HUS. Control and IL-10 lacking mice (IL-10 −/− ) were intravenously injected with Stx type 2 (Stx2) and survival rate was evaluated. PMN and circulating and renal pro- and anti-inflammatory factors were analyzed by FACS and enzyme-linked immunosorbent assay (ELISA) respectively. IL-10 −/− mice showed a higher survival associated with lower renal damage reflected by reduced plasma urea and creatinine levels than control mice. Circulating PMN increased at 72 h in both mouse strains accompanied by an up-regulation of CD11b in control mice. In parallel, renal PMN were significantly increased only in control mice after toxin. Plasma TNF-α, IL-6 and corticosterone levels were higher increased in IL-10 −/− than control mice. Simultaneously renal TNF-α raised constantly but was accompanied by increased TGF-β levels in IL-10 −/− mice. These results demonstrate that the profile of circulating and renal cytokines after Stx2 differed between strains suggesting that balance of these factors could participate in renal protection. We conclude that IL-10 absence has a protective role in an experimental model of HUS by reducing PMN recruitment into kidney and renal damage, and increasing mice survival.